EPISTEMOLOGI POLITIK ISLAM TENTANG WEWENANG DAN KEKUASAAN - Azhar, Muhammad (Muhammadiyah University Press, 2013)
The concept of authority and dominance bore political intrigues among Muslimcommunity throughout the history. The two concepts bore creative tense between Islamicpolitics that had Makkiyah characteristics that was myth-theological and Maddaniyah onethat was rational. After the prophet and the expansion of Islam, the Islamic dominancetended to be tyrannical. The application of the authority and dominance bore Islamicgovernment style that was repressive ((qawÃ£n)n siyÃ£siyyah) andrational (siyÃ£sah âaqliyyah)also the government stylethat had religious characteristics or caliphate (siyÃ£sah diniyyah).WhileAsy-SyÃ£tibi focused more on political dimension that had orientation on maqÃ£Ã¾idasy-syariâah and maslahah âÃ£mmah aspects. The next step emerged various interpretationsabout imamah, wilayah, khilafah, ummah, syura, amir concepts up to baiâah and jihad. Inpsychological-sociological manner, the sacred dominance became unhindered.Key words: Caliphate, Imamah, Amir, Wilayatul Faqih, Syuradan Nation StateKonsep wewenang dan kekuasaan melahirkan intrik politik di kalangan umatsepanjang sejarah. Dua konsep tersebut melahirkan ketegangan kreatif antara politikIslam yang bercorakMakkiyyah yang mitis-teologis dan Madaniyyah yang rasionalistik.Pasca era Nabi kekuasan Islamcenderung tiranik setelah adanya perluasan kekuasaanIslam.Aplikasi wewenang dan kekuasaan melahirkan style pemerintahan Islam yangrepresif (qawÃ£n)n siyÃ£siyyah), rasional (siyÃ£sah âaqliyyah) dan yang bercorak agamisatau khilafah (siyÃ£sah diniyyah).Sedangkan Asy-SyÃ£tibi) lebih memfokuskan padadimensi politik yang lebih berorientasi pada aspek maqÃ£Ã¾id asy-syariâah dan maslahahâÃ£mmah.Pada tahap selanjutnya muncul berbagai interpretasi tentang konsep-konsep:imamah, wilayah, khilafah, ummah, syura, amir, hingga baiâah dan jihad. Secarapsikologis-sosiologis, sakralitas kekuasaan menjadi tak terhindarkanKata Kunci: Khilafah, Imamah, Amir, Wilayatul Faqih, Syura dan Nation State